Analisis Penerapan Tax Amnesty Terhadap Rasio Pajak Secara Nasional Dan Regional (Kabupaten Dan Kota Serang, Kabupaten Lebak, Pandeglang & Kota Cilegon) - Darma, Sapta Setia; Sudarti, Zulva (AKUNTOTEKNOLOGI : JURNAL ILMIAH AKUNTANSI DAN TEKNOLOGI, 2023)
This study aims to examine the Tax Amnesty policy on national and regional tax ratios (Cilegon, Serang, Pandeglang & Lebak). Tax Amnesty is a government program in the form of granting forgiveness to taxpayers for mistakes they have made based on obligations that should have been implemented up to the 2015 tax year. The Tax Amnesty Policy implemented in 2016, the goals to be achieved are growth in tax sector income, tax database, & tax ratios. And the success of this program can be seen from the analysis of tax revenues, tax databases & gross domestic product (GDP) during the pre and post effective period of the tax amnesty program. Therefore this study aims to determine the growth of the tax ratio before and after the 2016 tax amnesty policy nationally and regionally and compare the results. This study uses the method, namely data on tax revenues and national and regional gross domestic product in the pre and post tax amnesty years of 2016, then compares the two to measure the growth of the tax ratio. This study shows the results that the implementation of the tax amnesty program cannot increase the tax ratio nationally, but regionally on the contrary & increases the growth of the average tax ratio regionally to nationally.